Estudo Fitoquímico de Geoffroea spinosa Jacq. (Leguminosae) - Lopes, Elton Luz (2008)
This work describes the identification of volatile constituents from leaves and flowers of Geoffroea spinosa Jacq. and the isolation of non-volatile constituents of its stem bark, stem wood, and root wood. This specie occurs on the riversides in Northeast Brazil and produces fruits which can be used as food. Its flowers are usually used in the form of tea to heal diarrhea and menstrual disorders. In spite of G. spinosa to be very important to the Northeastern people, as far as we know, any paper about its phytochemistry study was up to now published. The Lauric (66,54%), capric (15,39%) and miristic (13,11%) acids were the major compounds in the essential oils of its flowers, while its leaves presented palmitic acid (24,93%) and the diterpenes geranil linanool (14,97%) and phytol (17,86%) in higher concentration. The evaluation of the biological activity from the flowers of G. spinosa presented a significant nematicidal activity against the Meloidogyne incognita , but in the opposite, the volatile material of its leaves was inactive against the same nematode. The chromatographic analyses of the ethanolic extracts of the stem bark and stem wood allowed the isolation of lupeol and sucrose, respectively and the study of ethanolic extract of the root bark resulted the isolation of a mixture of -sitosterol, stigmasterol and their glycosides in addition of the oleanan triterpene, the 3- -acetoxiolean-12-en-28-oic acid, and a lactone called 3-hydroxy-1,5-dioxaciclohentriacontan-6-one. The last one never had been describe in the literature. The structural determination of the isolated metabolites, was performed by using Nuclear Magnetic Resonance of Hydrogen-1 and Carbon-13 (13C and 1H NMR - uni and two-dimensional). The oils were analyzed by GCL/MS and the identification of the components was initially done by using a MS library search with retention indices as a pre-selection routine followed by visual confirmation to reported standard MS data obtained from literature.